A Survey of Indonesian Students’ Use of Dictionaries - Fallianda, Fallianda (Lexikos, 2020)
This article aims to define the profile of Indonesian speakers as dictionary users by using a questionnaire-based research. The survey was distributed to university students who were studying English as a foreign language. The students fall in two groups with pre-intermediate and intermediate levels of English proficiency. They were instructed to fill out the survey. The question items encourage students to report their consultation frequency of dictionary use, dictionary choices and ratings, and needs of dictionary information. The findings confirmed that both pre-intermediate and intermediate students use bilingual dictionaries more often than monolingual dictionaries. The two groups show indifference towards the evaluation of different dictionary types, since learners rate bilingual dictionaries as good as monolingual dictionaries. The collected data offers insights into students’ awareness and knowledge of various dictionary types in Indonesian lexicographical context.